Cognitive bias modification to prevent depression (COPE): study protocol for a randomised controlled trial - Almeida, Osvaldo P (BioMed Central, 2014)
BACKGROUND: Depression is a leading cause of disability worldwide and, although efficacious treatments are available, their efficacy is suboptimal and recurrence of symptoms is common. Effective preventive strategies could reduce disability and the long term social and health complications associated with the disorder, but current options are limited. Cognitive bias modification (CBM) is a novel, simple, and safe intervention that addresses attentional and interpretive biases associated with anxiety, dysphoria, and depression. The primary aim of this trial is to determine if CBM decreases the one-year onset of a major depressive episode among adults with subsyndromal depression. DESIGN AND METHODS: This randomised controlled trial will recruit 532 adults with subsyndromal symptoms of depression living in the Australian community (parallel design, 1:1 allocation ratio). Participants will be free of clinically significant symptoms of depression and of psychotic disorders, sensory and cognitive impairment, and risky alcohol use. The CBM intervention will target attentional and interpretive biases associated with depressive symptoms. The sessions will be delivered via the internet over a period of 52 weeks. The primary outcome of interest is the onset of a major depressive episode according the DSM-IV-TR criteria over a 12-month period. Secondary outcomes of interest include change in the severity of depressive symptoms as measured by the Patient Health Questionnaire (PHQ-9), use of antidepressants or benzodiazepines, and changes in attention and interpretive biases. The assessment of outcomes will take place 3, 6, 9, and 12 months after randomisation and will occur via the internet. DISCUSSION: We propose to test the efficacy of an innovative intervention that is well grounded in theory and for which increasing empirical evidence for an effect on mood is available. The intervention is simple, inexpensive, easy to access, and could be easily rolled out into practice if our findings confirm a role for CBM in the prevention of depression. TRIAL REGISTRATION: Australian and New Zealand Clinical Trials Registry ACTRN12613001334796. Date: 5th December 2013.